2018
DOI: 10.3168/jds.2017-13172
|View full text |Cite
|
Sign up to set email alerts
|

Bioeconomics of sexed semen utilization in a high-producing Holstein-Friesian dairy herd

Abstract: A bioeconomic, stochastic spreadsheet model, that included calculation of the net present value of the additional value of all future descendants resulting from increased selection intensity, was developed to study the profitability of using sexed semen in a high input-high output dairy herd. Three management strategies were modeled: (1) only heifers inseminated with sex-sorted semen and cows inseminated with unsorted semen; (2) both heifers and cows inseminated with sex-sorted semen; and (3) a reference scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…Male calves generally have a little economic income in the dairy herds; thus, the use of sex‐sorted semen is preferred for increasing the number of female calves which are used as replacement heifers afterwards (Cottle, Wallace, Lonergan, & Fahey, 2018; Crites et al., 2018). Besides, several studies have reported that sex‐sorted semen increases economic profitability (Chebel, Guagnini, Santos, Fetrow, & Lima, 2010) and that sex‐sorted semen technology had also considerable benefits such as acceleration genetic gain (Hohenboken, 1999), enhanced herd biosecurity (Cottle et al., 2018), lower animals participating in the progeny test (De Vries et al., 2008) and reduction in the incidence of dystocia (Holden & Butler, 2018). The lower fertility of sex‐sorted semen is the main factor that limits widespread use in dairy herds (DeJarnette et al., 2011), which has been discussed in many reviews (Grant & Chamley, 2007; Holden & Butler, 2018; Seidel, 2007; Vishwanath & Moreno, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Male calves generally have a little economic income in the dairy herds; thus, the use of sex‐sorted semen is preferred for increasing the number of female calves which are used as replacement heifers afterwards (Cottle, Wallace, Lonergan, & Fahey, 2018; Crites et al., 2018). Besides, several studies have reported that sex‐sorted semen increases economic profitability (Chebel, Guagnini, Santos, Fetrow, & Lima, 2010) and that sex‐sorted semen technology had also considerable benefits such as acceleration genetic gain (Hohenboken, 1999), enhanced herd biosecurity (Cottle et al., 2018), lower animals participating in the progeny test (De Vries et al., 2008) and reduction in the incidence of dystocia (Holden & Butler, 2018). The lower fertility of sex‐sorted semen is the main factor that limits widespread use in dairy herds (DeJarnette et al., 2011), which has been discussed in many reviews (Grant & Chamley, 2007; Holden & Butler, 2018; Seidel, 2007; Vishwanath & Moreno, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies show that the blastocyst rates are lower than those obtained with conventional semen (Seidel Jr. 2014). On the other hand, Cottle et al (2018) identified a significant profit advantage for using sexed semen in the context of a high-output, dairy system of spring births in Ireland. The authors concluded that the use of sexed semen is more appropriate for those farms that already have an excellent fertility performance.…”
Section: Use Of Sexed Semen and Its Advantagesmentioning
confidence: 99%
“…The authors concluded that the use of sexed semen is more appropriate for those farms that already have an excellent fertility performance. Thus, the lowest rates associated with sexed semen can be less acceptable for farms with sub-optimal dairy herds fertility (Cottle et al, 2018).…”
Section: Use Of Sexed Semen and Its Advantagesmentioning
confidence: 99%
“…The process enables the separation of X-and Y-bearing spermatozoa with 90% accuracy, allows farmers to maintain their herds without having to buy cows from other sources and increases herd milk production through the manipulation of sex ratios 33,46 . However, sorting takes approximately 50 h to sort through a single bull ejaculate (sorting speed: 30,000 sperm/s) and the resulting straws are more expensive than unsorted straws 46,47 . Further to that, there is a 7.5-fold decrease in the sperm concentration of sexed straws as sperm are diluted due to sorting and centrifugation and 50% of the sperm are discarded 48 .…”
mentioning
confidence: 99%